2018
DOI: 10.1039/c7tc05571d
|View full text |Cite
|
Sign up to set email alerts
|

Vertical CNT–Ecoflex nanofins for highly linear broad-range-detection wearable strain sensors

Abstract: A nanofin-based strain sensor, fabricated by transferring vertical CNTs to an Ecoflex substrate, has the advantages of high linearity and sensitivity and can detect both large and subtle motions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 40 publications
1
48
0
2
Order By: Relevance
“…[230,232] Zhang et al have reported that sandwiching CNTs-Ecoflex nanocomposite strain sensors between two layers of Ecoflex can greatly enhance their endurance to humidity variations. [233] Second, conformal adhesion of wearable strain sensors onto the soft skin is another important consideration for noise-free and accurate strain monitoring. [190] The weak interfacial adhesion between wearable sensors and skin leads to their sliding and delamination from the skin.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…[230,232] Zhang et al have reported that sandwiching CNTs-Ecoflex nanocomposite strain sensors between two layers of Ecoflex can greatly enhance their endurance to humidity variations. [233] Second, conformal adhesion of wearable strain sensors onto the soft skin is another important consideration for noise-free and accurate strain monitoring. [190] The weak interfacial adhesion between wearable sensors and skin leads to their sliding and delamination from the skin.…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…The closest any material comes to the desired benchmark values for the optimum material is again a highly aligned/orientated CNT composite with G = 4, W = 2.5, Y = 125 kPa. [74]…”
Section: Gauge Factor Vs Young's Modulus and The Lay Of The Landmentioning
confidence: 99%
“…CNTs have been broadly studied for wearable strain sensing. [106][107][108] For example, a millimeter-long multiwalled CNT film, prepared by stacking CNT webs drawn from a CNT array, was utilized for motion detection. [106] The unidirectionally aligned CNT layer provided high stretchability and large gauge factor.…”
Section: Physical Sensingmentioning
confidence: 99%